Knowledge and Attitude of Teachers about Communicable Diseases in some of Primary Schools in Erbil - Abdulqader Hussein; Nazar A. Sheren; Kareem Fatah (Kufa Journal for Nursing Sciences)
Background: Infectious diseases, or communicable diseases comprise clinically evident illness, characteristic medical signs and/or symptoms of disease resulting from the infection, presence and growth of pathogenic biological agents in an individual host organism. In certain cases, infectious diseases may be asymptomatic. School health programs could not be fully implemented without having staff, teachers, and parent's cooperation and involvement.